"He's not heavy, he's an anchor baby": Fat children, failed futures, and the threat of Latina/o excess. Issue 2 (2nd July 2016) - Dame-Griff, E. Cassandra
ABSTRACT: This article examines how First Lady Michelle Obama's Latina/o-focused speeches, as part of the Let's Move! campaign, intersect with anti-immigrant rhetoric and reproduce discourses characterizing Latinas as "bad" mothers. This discourse renders Latina/o children contingent citizens whose potential place in the nation-state depends on their "achievement" of an acceptably sized body as well as their future utility to the nation-state in the form of military service. Latina/o children's failure in this state-backed/mandated weight-loss project shifts the discourse of future citizenship to one of threat to the nation-state. In applying conceptual frames from fat studies to discourse regarding Latinas/os, this article connects anti-fat and anti-Latina/o immigrant discourse, exploring how discursive constructions of excess shape idea(l)s of belonging and citizenship.